Norwegian Educational Psychological Service Advisors' Perspectives and Practices in Supporting Immigrant Students in Primary Schools in Norway - Norozi, Sultana Ali (Social Education Research, 2026)
In light of increasing migration to Europe, providing educational support for immigrant students, especially those needing special assistance, has become crucial. In Norway, the Educational Psychological Service (EPS) plays a key role in supporting students with special needs. This paper explores EPS advisors' perspectives and practices in assessing immigrant students in Norwegian primary schools through interviews with eight advisors. The research highlights challenges and perspectives related to working with immigrant students, drawing on Bronfenbrenner's Ecological Systems Theory and special education theories. The findings reveal that although EPS advisors understand the unique needs of immigrant students and recognize the importance of cultural differences, they experience challenges in applying this knowledge in practice. The study underscores the need for alternative approaches and tools to better support immigrant students and foster inclusive education. By addressing the challenges faced by the EPS advisors, the education system in Norway can foster a more inclusive and supportive environment for special needs immigrant students, ensuring their optimal learning and development. This study relies solely on EPS advisors' personal understanding of their work. Therefore, further research incorporating the perspectives of teachers and mother tongue instructors is needed.